Evaluation of the Safety and Efficacy of Coronary Intravascular Lithotripsy for Treatment of Severely Calcified Coronary Stenoses: Evidence From the Serial Disrupt CAD Trials - Liang, Bo; Gu, Ning (Frontiers in Cardiovascular Medicine, 2021)
Background: Previous understanding holds that rotational atherectomy and modified balloons remain the default strategy for severely calcified coronary stenoses. In recent years, coronary intravascular lithotripsy (IVL) provides new ideas. This study was conducted to evaluate the safety and efficacy of IVL for the treatment of severely calcified coronary stenoses. Methods: The serial Disrupt CAD trials (Disrupt CAD I, Disrupt CAD II, Disrupt CAD III, and Disrupt CAD IV) were included in this study. The safety endpoint was freedom from major adverse cardiovascular events (MACE) in hospital, at 30 days, and at 6 months following the index procedure. The efficacy endpoints included procedural success and angiographic success. Optical coherence tomography (OCT) was used to evaluate the mechanism of action of IVL quantifying the coronary artery calcification (CAC) characteristics and calcium plaque fracture. Results: We enrolled a total of 628 patients with a mean age of 71.8 years, 77.1% males. In these patients, the left anterior descending artery and right coronary artery were the most vulnerable vessels. The diameter stenosis was 64.6 ± 11.6% and the lesion length was 24.2 ± 11.4 mm. IVL had a favorable efficacy (93.0% procedural success, 97.5% angiographic success, and 100.0% stent delivery). Among the 628 patients, 568, 568, and 60 reported MACE endpoints in hospital, at 30 days, and at 6 months, respectively. The results showed that 528, 514, and 55 patients were free from MACE in hospital, at 30 days, and at 6 months, respectively. OCT measurements demonstrated that calcium fracture was the underlying mechanism of action for coronary IVL. Conclusions: IVL is safe and efficient for severely calcified coronary stenoses, and, importantly, calcium fracture facilitated increased vessel compliance and favorable stent expansion.